2005
DOI: 10.1104/pp.104.058040
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid Homeostasis in Arabidopsis Is Ensured by Feedback Expressions of Multiple Genes Involved in Its Metabolism

Abstract: Homeostasis of brassinosteroids (BRs) is essential for normal growth and development in higher plants. We examined responsiveness of 11 BR metabolic gene expressions to the decrease or increase of endogenous BR contents in Arabidopsis (Arabidopsis thaliana) to expand our knowledge of molecular mechanisms underlying BR homeostasis. Five BR-specific biosynthesis genes (DET2, DWF4, CPD, BR6ox1, and ROT3) and two sterol biosynthesis genes (FK and DWF5) were upregulated in BR-depleted wild-type plants grown under b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
195
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(214 citation statements)
references
References 45 publications
18
195
1
Order By: Relevance
“…Biosynthesis and inactivation are coordinated via BR-dependent transcriptional control of the genes involved in both processes. All BR-biosynthetic P450 genes of Arabidopsis are under negative feedback regulation by active BRs (Bancos et al, 2002;Tanaka et al, 2005), whereas of those encoding inactivating enzymes only BAS1 was found BR inducible (Choe et al, 2001;Takahashi et al, 2005). Feedback regulation of CPD is abolished in the BR-insensitive bin2 and brassinosteroid insensitive 1-2 (bri1-2)/cbb2 mutants (Li et al, 2001;Bancos et al, 2002), indicating a key role of BR signaling in the hormonal self-regulation of BR biosynthesis and perhaps also inactivation.…”
mentioning
confidence: 91%
“…Biosynthesis and inactivation are coordinated via BR-dependent transcriptional control of the genes involved in both processes. All BR-biosynthetic P450 genes of Arabidopsis are under negative feedback regulation by active BRs (Bancos et al, 2002;Tanaka et al, 2005), whereas of those encoding inactivating enzymes only BAS1 was found BR inducible (Choe et al, 2001;Takahashi et al, 2005). Feedback regulation of CPD is abolished in the BR-insensitive bin2 and brassinosteroid insensitive 1-2 (bri1-2)/cbb2 mutants (Li et al, 2001;Bancos et al, 2002), indicating a key role of BR signaling in the hormonal self-regulation of BR biosynthesis and perhaps also inactivation.…”
mentioning
confidence: 91%
“…Thus, the phosphorylation status of BES1 and/or BZR1 has been used as a direct biochemical marker for BR signaling outputs (18). BZR1 and BES1 can bind directly to the promoter regions of the BR biosynthetic genes, CPD and DWF4, and inhibit their expression, forming a negative feedback loop (25,29). Therefore, the transcript levels of CPD and DWF4 are excellent molecular markers, and have been widely used for determining the strength of BR signaling outputs (18).…”
mentioning
confidence: 99%
“…Reduced expression of the genes associated with secondary metabolism may partially contribute to the observed decrease in membrane integrity under high temperatures for Sicala 45 (Cottee et al 2012). This may limit photosynthetic capacity (Sullivan 1971) and subsequently reduced tolerance to nutrient (Ryan et al 2007) and heat stress (Tanaka et al 2005).…”
Section: Cultivar Differences For Expression Of Energy Productionassomentioning
confidence: 99%